Corporate Valuation: The Impact of Dividend Governance Interaction with Earnings Performance as a Moderator: English - Euclea Theda Ethelind; Meythi Meythi; Riki Martusa; Rapina Rapina (Owner : Riset dan Jurnal Akuntansi, 2026)
This paper explores the impact of dividend governance interactions on firms' value and focuses on the moderating effect of Earnings Performance. This study includes government owned banks and national commercial banks quoted in the Indonesia Stock Exchange. This study extends the prior research by investigating the interrelationship among dividend governance interactions, Earnings Performance, and company value. The Price Book Value (PBV) is an empirical discourse of the company book value and the dividend governance interaction is tested for the Dividend Payout Ratio (DPR). The analysis is based on data from the Refinitiv Eikon platform. ROE can act as an indicator of financial performance. A cross sectional analysis of the comparison of government and private banks was done. The findings indicate that dividend governance interaction is more pronounced in government banks compared to private banks. This is a validation of how it is in the environment, how the environment works and what properties it has.